An EAP curriculum design of a content and language integrated learning program for hospitality students in Taiwan - Hsiao-I Hou (Universidad de La Sabana, 2013)
Although there are many pedagogical approaches to teaching English for Academic Purposes (EAP), most share the objective of preparing second language (L2) learners to engage academic study. This paper reports the findings of a case study that explores the approach to the development and features of a content-and-language integrated learning (CLIL) program at a hospitality university in Taiwan. The study describes the theoretical basis of the program and its relation to background and study rationale. Additionally, program development and implementation processes are described. The data were collected during an academic year with a combination of quantitative and qualitative methods including pre- and post- tests, a student questionnaire, field notes, and semi-structured interviews. The research results show that students in the higher performance group (HP) and the lower performance group (LP) have different opinions regarding selected materials, assigned homework to content knowledge learning, English instruction to content knowledge learning, and difficulties with the written tests. The research results are also consistent with previous studies. Practical implications for theory, practice, and future research are also discussed.